Short‐term plasticity regulates the excitation/inhibition ratio and the temporal window for spike integration in CA1 pyramidal cells. (23rd April 2015) - Bartley, Aundrea F.; Dobrunz, Lynn E.
Abstract Many neurodevelopmental and neuropsychiatric disorders involve an imbalance between excitation and inhibition caused by synaptic alterations. The proper excitation/inhibition (E/I) balance is especially critical in CA1 pyramidal cells, because they control hippocampal output. Activation of Schaffer collateral axons causes direct excitation of CA1 pyramidal cells, quickly followed by disynaptic feedforward inhibition, stemming from synaptically induced firing of GABAergic interneurons. Both excitatory and inhibitory synapses are modulated by short‐term plasticity, potentially causing dynamic tuning of the E/I ratio. However, the effects of short‐term plasticity on the E/I ratio in CA1 pyramidal cells are not yet known. To determine this, we recorded disynaptic inhibitory postsynaptic currents and the E/I ratio in CA1 pyramidal cells in acute hippocampal slices from juvenile mice. We found that, whereas inhibitory synapses had paired‐pulse depression, disynaptic inhibition instead had paired‐pulse facilitation (≤ 200‐ms intervals), caused by increased recruitment of feedforward interneurons. Although enhanced disynaptic inhibition helped to constrain paired‐pulse facilitation of excitation, the E/I ratio was still larger on the second pulse, increasing pyramidal cell spiking. Surprisingly, this occurred without compromising the precision of spike timing. The E/I balance regulates the temporal spike integration window from multiple inputs; here, we showed that paired‐pulse stimulation can broaden the spike integration window. Together, our findings show that the combined effects of short‐term plasticity of disynaptic inhibition and monosynaptic excitation alter the E/I balance in CA1 pyramidal cells, leading to dynamic modulation of spike probability and the spike integration window. Short‐term plasticity is therefore an important mechanism for modulating signal processing of hippocampal output.